New Straits Times, 15 November 2011 - Kasmiah Mustapha; Carisma Kapoor; Punitha Kumar; Syed Umar Ariff (The New Straits Times Press (M) Bhd, 2011)
Treatment important: Those with HIV and AIDS also contribute to the rising number of TB cases.